Kyrgyz Republic Economic Report, October 2013 : Growth is Back, Headwinds Persist - World Bank (World Bank, Washington, DC, 2017)
This regular economic report records the economic activities of Kyrgyz Republic for the year 2013. The growth performance of the Kyrgyz Republic has been encouraging and largely in line with our forecasts from the Spring 2013 update. Real Gross domestic product (GDP) expanded by 8 percent in the first eight months of 2013 (year-on-year) driven by a recovery in gold production at the Kumtor mine. The non-gold economy also performed well, as strong private transfers from abroad and higher credit to the private sector fueled private consumption and investment. At the same time, the contribution of the public sector was more limited with government spending kept under control. Following a slow start, officially recorded exports have started to recover. Macroeconomic policies have been supportive of stability and stronger economic activity. The baseline scenario for 2014 remains optimistic, though headwinds have been gaining strength. The challenge to sustain high economic growth rates in the medium term is considerable. Monetary policy needs to be cautious to prevent the build-up of risks in the financial sector and limit inflationary pressures. Second, creation of a vibrant and competitive private sector will require significant upgrading of the country’s institutional, physical and human capital. A business environment characterized by efficient institutions, reliable infrastructure and highly-skilled labor will help realize the country’s growth potential and reduce poverty.